Little Town on the Prairie - Wilder, Laura Ingalls; williams, grath (US harperCollins, 1981)
The little settlement that weathered the long, hard winter of 1880-81 is now a growing town. Laura is growing up, and she goes to her first evening social. Mary is at last able to go to a college for the blind. Best of all, Almanzo Wilder asks permission to walk home from church with Laura. And Laura, now fifteen years old, receives her certificate to teach school. And so continues Laura Ingalls Wilder's beloved story of a pioneer girl and her family. The nine Little House books have been cherished by generations of readers as both a unique glimpse into America's frontier past and a heartwarming, unforgettable story
English stories
2
Keywords: English stories